INSTAGRAM AS THE ONLINE TEACHING PLATFORM OF SPEAKING - Silalahi, Juniar Tiurma Uli; Perdana, Indra; Luardini, Maria Arina (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2021)
Speaking is considered as an important skill to be mastered by students in terms of communication need. However, speaking is categorized as a difficult skill to teach. Moreover, on this crucial situation of covid 19, the process of teaching and learning is conducted at home or called online learning. Therefore, it is important for the teacher in selecting an appropriate media for teaching speaking. Instagram platform can be selected by the teacher for teaching speaking. The method of this research is qualitative descriptive, and the data collection is interview and observation. This article aims to elaborate clearly the step of online teaching speaking by using Instagram platform. The result showed the step of teaching speaking are (1) allow the students to open their Instagram account, then let them to watch some videos on the wall of Instagram or in the live story. (2) asking the students to speak one by one based on the video their watched. For example, a students to watch video about share experience, so the students should also speak for telling her experience, and give them limit time to speak. (3) give correction towards the students related to how to pronounce correctly. (4) ask the students to make some groups consist of 3 students. Then, teacher giving time to them to plan what they want to tell about their experience. (5) make video and share it on the instagram. However, Before starting to make the video, the students should make script of the topic they spoke.